2021
DOI: 10.1097/gme.0000000000001792
|View full text |Cite
|
Sign up to set email alerts
|

Weight regulation in menopause

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 59 publications
0
13
0
1
Order By: Relevance
“…Like other national studies, our findings showed the highest prevalence of obesity in the median age groups 35,36 . Particularly among women, weight gain is common in menopause 37 . Healthy diets combined with physical activity have shown beneficial effects in preventing menopause-related obesity 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Like other national studies, our findings showed the highest prevalence of obesity in the median age groups 35,36 . Particularly among women, weight gain is common in menopause 37 . Healthy diets combined with physical activity have shown beneficial effects in preventing menopause-related obesity 38 .…”
Section: Discussionmentioning
confidence: 99%
“…It is postulated that fat mass loss mediates the relationship between exercise and estrogen reduction through increased SHBG [ 38 , 39 , 40 ]. Given that fat cells produce most of the body’s endogenous estrogen after menopause, a connection between the two seems reasonable [ 41 ]. Increased circulating amounts of estrogen and/or insulin and IGF-1 may be one mechanism by which excess body fat promotes cancer development and progression in postmenopausal women (insulin-like growth factor) [ 42 , 43 ].…”
Section: Physical Activity and Cancermentioning
confidence: 99%
“…The American College of Sports Medicine defines power training as moving heavy weight at a fast speed [24]. At least 2 days per week of resistance training which targets all major muscle groups is recommended for these benefits [25].…”
Section: Movementmentioning
confidence: 99%